Stability and water solubility of calcium ferrite-type aluminum-rich phase: implications for deep water cycle caused by subducting basaltic crusts - Xinyue Zhang; Izumi Mashino; Takayuki Ishii (Progress in Earth and Planetary Science)
Abstract The subducting crustal materials serve as a crucial channel for transporting water to the lower mantle. Recent experimental studies suggest that crustal materials such as basaltic crust can be a main water carrier and reservoir playing an important role on water cycling in the lower mantle. Despite being a primary mineral in crustal materials, the water solubility of calcium ferrite-type (CF) phase and its stability are unclear yet. A recent phase relation study of hydrous basalts showed Na-depletion in lower-mantle minerals, suggesting the presence of fluid possibly with high Na concentration and the absence of CF phase along the low-temperature slab geotherms, where Al-rich hydrous phase H and ferropericlase appear instead. These phases could consequently produce Na-depleted CF phase when reaching the dehydration temperature of Al-rich hydrous phase H. In this study, we investigated the stability and water solubility of CF-type MgAl2O4, which is a main CF component in a hydrous basalt, in water-bearing systems at 26–32 GPa and 1200–1900 °C using a Kawai-type multi-anvil press. Our results indicate that the stability of the CF phase is strongly influenced by water content in the system. Water contents of recovered CF phases estimated by Fourier-transform infrared spectroscopy show a limited variation between 73 and 87 ppm wt at a pressure of 26 GPa and temperatures of 1500–1900 °C. We suggest that CF phase could not be a primary water carrier at lower mantle depths. This emphasizes contributions of hydrous aluminous silica minerals to Earth’s deep water cycling and heterogeneous structures in the lower mantle due to the strong water partitioning to this phase compared with other constituent minerals.